Promotion of Prescription Drugs and Its Impact on Physicians' Choice Behavior - Gönül, Füsun F.; Carter, Franklin; Petrova, Elina; Srinivasan, Kannan (Journal of Marketing, 2001)
The authors investigate whether and how pricing and promotional activities influence prescription choice behavior using a comprehensive panel of physicians and data on competitive price and promotional activities. The authors find that physicians are characterized by fairly limited price sensitivity, detailing and samples have a mostly informative effect on physicians, and physicians with a relatively large number of Medicare or health maintenance organization patients are less influenced by promotion than other physicians are.